Thermal degradation kinetics of LED lamps in step-up-stress and step-down-stress accelerated degradation testing. (25th August 2016) - Cai, Miao; Yang, Daoguo; Zheng, Jianna; Mo, Yuezhu; Huang, Jianlin; Xu, Jiwen; Chen, Wenbin; Zhang, Guoqi; Chen, Xianping
Highlights: Step-down-stress accelerated degradation testing (SDSADT) for LED lamps is proposed. The effects of stress orders on LED lamps between SDSADT and SUSADT are analyzed. The SDSADT can rapidly terminate the initial activation phase of LED products. The decay kinetics of a lamp with strong CHD is unrelated to historical loaded stress. Optical power decay exhibits a close correlation with tunneling saturation current. Abstract: Step-down-stress accelerated degradation testing (SDSADT) for light-emitting diode (LED) lamps is proposed. Meanwhile, achieving a solution to terminate the initial increase in the optical parameters of LED products rapidly is considered. The thermal degradation kinetics of LED lamps is investigated by SDSADT and step-up-stress accelerated degradation testing (SUSADT) to compare the decay effects of different thermal stress orders loaded in both tests. Two types of commercial LED lamps with different capabilities of heat dissipation (CHDs) are subjected to the investigation. Results show that the inherent initial improvement of the LEDs in SUSADT is more evident than that in SDSADT, and SDSADT can effectively alleviate the initial increase in the optical parameters of LED lamps. The thermal degradation kinetics of LED lamps with strong CHD is only related to the present loaded stress but unrelated to historical loaded stress. This finding is consistent with Nelson's assumption on step-stress testing. Furthermore, the packaging materials, which include phosphor and silicon layers, play an important role in the degradation of the entire LED package, followed by the degradation of the LED chip. Correlation analysis shows that the degraded optical power of stressed LEDs exhibits a close correlation with the drooped tunneling saturation current.